Investigation on the flotation behavior and adsorption mechanism of 3-hexyl-4-amino-1, 2, 4-triazole-5-thione to chalcopyrite. (April 2016) - Qu, Xiaoyan; Xiao, Jingjing; Liu, Guangyi; Liu, Sheng; Zhang, Zhiyong
Highlights: 3-Hexyl-4-amino-1, 2, 4-triazole-5-thione first introduced as a collector. HATT exhibits excellent performances for chalcopyrite flotation at pH 4–8. HATT adsorption on chalcopyrite is a spontaneously endothermic process. HATT–copper surface complexes are formed on chalcopyrite. Abstract: In this paper, a novel surfactant, 3-hexyl-4-amino-1, 2, 4-triazole-5-thione (HATT) is first introduced as a collector for chalcopyrite flotation. Its flotation behavior and adsorption mechanism to chalcopyrite has been evaluated by micro-flotation tests, and zeta potential, FTIR spectra and adsorption quantity measurements. The results demonstrate that HATT exhibited excellent flotation performances to chalcopyrite at pH 4–8. The adsorption of HATT on to chalcopyrite agrees well with the pseudo-second-order model and Langmuir isotherm, and is a spontaneously endothermic chemisorption process. FTIR spectra and zeta potential analyses further imply that chalcopyrite might chemisorb HATT by formation of HATT–copper surface complexes.